Análise palinotaxômica e bioestratigráfica da subturna monosaccites na Bacia do Paraná, Brasil : II: gêneros costatascyclus, circumplicatipollis, caheniasaccites, stellapollenites e divarisaccus - Félix, Cristina Moreira (2008)
This paper presents a taxonomic and biostratigraphic analysis of the monosaccate pollen grains related to the genera Costatascyclus Felix & Burbridge emend. Urban 1971, Circumplicatipollis Ottone & Azcuy 1988, Caheniasaccites Bose & Kar 1966, Stellapollenites Lele 1965 and Divarisaccus Venkatachala & Kar 1966 recorded in the Pensylvannian - Permian interval in the Paraná Basin. These genera are represented by seven species: Costatascyclus crenatus Felix & Burbridge 1967, Circumplicatipollis plicatus Ottone & Azcuy 1988, Caheniasaccites flavatus Bose & Kar 1966, Caheniasaccites elongatus Bose & Kar 1966, Caheniasaccites verrucosus (González-Amicón) Gutiérrez 1993, Stellapollenites talchirensis Lele 1965 and Divarisaccus stringoplicatus Ottone 1991. Among these species, C. verrucosus is recorded for the first time to the Paraná Basin. Based on analysis of samples from new localities, new slides of published sections, from scientific collections, and on the examination of available papers, synonymic lists are shown, modifying the ranges of certain species. Respective occurrences of the taxa in the other Brazilian intracratonic basins (Amazonas and Parnaíba) are also analyzed. Furthermore, main morphologic distinctive characters of these species are presented, to facilitate the identification and their use in biostratigraphic and paleoenvironmental analysis.